Pain perception in humans: use of intraepidermal electrical stimulation. Issue 5 (3rd December 2011) - Inui, Koji; Kakigi, Ryusuke
Abstract : The choice of a system specific stimulus is difficult when investigating the human nociceptive system, in contrast with the tactile, auditory and visual systems, because it should be noxious but not actually damage the tissue. The discomfort accompanying system specific stimulation must be kept to a minimum for ethical reasons. In this review, recent progress made in the study of human pain perception using intraepidermal electrical stimulation (IES) is described. Also, whether IES is a viable alternative to laser stimulation is discussed. IES selectively activates Aδ nociceptors, elicits a sharp pricking sensation with minimal discomfort and evokes cortical responses almost identical to those produced by laser stimulation. As IES does not require expensive equipment, and is easy to control, it would seem useful for pain research as well as clinical tests.